Meaningful learning with mobile devices: pre-service class teachers’ experiences of mobile learning in the outdoors - Kärki T.; Keinänen H.; Tuominen A.; Hoikkala M.; Matikainen E.; Maijala H. (Routledge, 2022)
The authors consider the use of mobile learning environment ActionTrack in teacher education. Pre-service class teachers’ (N = 277) experiences of the mobile learning environment were measured with a 7-point Likert-scale questionnaire based on seven attributes of meaningful learning. Students’ ratings for different attributes were analysed quantitatively. The authors conclude that, based on this analysis, it is possible to create meaningful learning experiences using ActionTrack. All the measured attributes of meaningful learning obtained positive values. In the mobile learning events of this study, three attributes arose as the essential features: mobile learning in the outdoors was primarily considered collaborative, active and contextual.